Colliding Wave Solutions in a Symmetric Non-Metric Theory - Gürtuğ, Özay; Halilsoy, Mustafa (Springer US, 2009)
A method is given to generate the non-linear interaction (collision) of linearly polarized gravity coupled torsion waves in a non-metric theory. Explicit examples are given in which strong mutual focussing of gravitational waves containing impulsive and shock components coupled with torsion waves does not result in a curvature singularity. However, the collision of purely torsion waves displays a curvature singularity in the region of interaction.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Physics, Physics, general, Mathematical and Computational Physics, Colliding gravitational waves, Torsion waves, Quantum Physics, Elementary Particles, Quantum Field Theory